Organizing Material Programs to Improve the Character of Children at TPA Baitul Hikmah - Abdul Haris Muchtar; Mariah; Risman Nugraha; Ardi Pratama; Ratunoor Nabila Zahra; Pamela Nawal Iman Fadhilla; Wirandi Saputra; Rizki Wandan Sitorus; Audy Putri Adinda; Ahmad Zaid Alvatir; Mushab Fathan Athali; Muhammad Nafis (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
This study aims to develop program materials focused on enhancing the character of children attending Baitul Hikmah TPA. It endeavors to contribute positively to the moral and ethical development of children within the TPA setting. The research methodology involves creating tailored program materials aimed at fostering character development while considering relevant moral and cultural values. Participants include children from the specified age group at Baitul Hikmah TPA. The program materials will adopt an interactive and creative approach to ensure active participation of the children in the learning process. Evaluation of the program will include participant observation, character assessments, and feedback from TPA parents and teachers. The research endeavors to provide fresh insights into the efficacy of program materials in enhancing the character of children within TPA. Furthermore, it aims to offer practical implications that could serve as a foundation for similar programs in comparable educational institutions, thereby extending the positive impact on character development within the realm of religious and moral education.